2017
DOI: 10.1088/1741-2552/aa843e
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of the skull for human neuromodulation with transcranial focused ultrasound

Abstract: Objective. Transcranial focused ultrasound is an emerging field for human non-invasive neuromodulation, but its dosing in humans is difficult to know due to the skull. The objective of the present study was to establish modeling methods based on medical images to assess skull differences between individuals on the wave propagation of ultrasound. Approach. Computational models of transcranial focused ultrasound were constructed using CT and MR scans to solve for intracranial pressure. We explored the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 53 publications
12
116
0
Order By: Relevance
“…Detailed computational models of the skull are used in applications including aberration correction in high intensity focused ultrasound for thermal ablation (Marquet et al, ) and nonthermal ablation with microbubble enhanced focused ultrasound (Top, White, & McDannold, ). We were not able to acquire CT scans of the participants in this study and given the initial model shown here (despite a good conservation of beam geometry) it is recommended for future subcortical single‐element transcranial ultrasound studies that CT scans of individuals are acquired and detailed computational models run to ensure accurate target localization and transducer placement (Mueller et al ). This may not be feasible in some cases or not recommended to expose participants to unnecessary ionizing radiation.…”
Section: Limitations and Considerationssupporting
confidence: 77%
See 2 more Smart Citations
“…Detailed computational models of the skull are used in applications including aberration correction in high intensity focused ultrasound for thermal ablation (Marquet et al, ) and nonthermal ablation with microbubble enhanced focused ultrasound (Top, White, & McDannold, ). We were not able to acquire CT scans of the participants in this study and given the initial model shown here (despite a good conservation of beam geometry) it is recommended for future subcortical single‐element transcranial ultrasound studies that CT scans of individuals are acquired and detailed computational models run to ensure accurate target localization and transducer placement (Mueller et al ). This may not be feasible in some cases or not recommended to expose participants to unnecessary ionizing radiation.…”
Section: Limitations and Considerationssupporting
confidence: 77%
“…CT images were used to construct the acoustic model of the skull, while MR images were used to target tFUS at the unilateral sensory thalamus based upon individual brain morphology. Details of the modelling parameters can be found in Mueller, Ai, Bansal, and Legon (2017).…”
Section: Quantitative Modeling Of Ultrasound Wave Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…The CT images of the Wistar rat were aquired from the scan using a Siemens Inveon microCT machine at the University Imaging Center of the University of Minnesota. The simulation study was following a similar protocol described in (Mueller et al, 2017) and using the acoustic parameters listed in Table 2. The skull was deemed to be immersed in water and its acoustic properties were mapped from the Hounsfield unit acquired from the CT images and thus the porosity readings.…”
Section: Eq2mentioning
confidence: 99%
“…[11,12] TPS extends current literature by providing a new navigated stimulation technique which is clinically certified (CE mark). [14,15] We also present the first patient study (Alzheimer's disease, AD) and first investigation of long-term effects (up to three months) for ultrasound brain stimulation. [14,15] We also present the first patient study (Alzheimer's disease, AD) and first investigation of long-term effects (up to three months) for ultrasound brain stimulation.…”
Section: Introductionmentioning
confidence: 99%